비침습눈물막파괴시간이 각막곡률계측의 재현성에 미치는 영향 - 신혜은; 정소연; 정지원 (Daihan angwa haghoi jabji, 2023)
목적: 건성안 환자에서 KeratographⓇ5M (K5M)을 사용하여 평가한 비침습눈물막파괴시간(non-invasive keratograph break-up time, NIKBUT)이 K5M으로 측정한 각막곡률계측의 재현성에 미치는 영향을 평가하고자 한다. 방법: 건성안 환자 36명과 대조군 30명에서 두 번씩 측정한 각막곡률 값의 재현성을 평가하였고, 두 군사이에 두 번씩 측정한 각막곡률 값의 차이의 절대값이 0.5 diopter (D)를 넘는 비율에 차이가 있는지 분석하였으며, 건성안 환자에서 NIKBUT와 각막곡률 값 차이의 절대값 사이의 상관성을 평가하였다. 결과: 건성안 환자에서 K5M으로 측정한 최대각막곡률을 제외한 각막곡률 값 및 난시값의 급내상관계수는 0.95 이상이었으나 대조군에비해서는 낮은 수치를 보였고 편평한 각막곡률과 최대각막곡률 값의 차이의 절대값이 0.5 D를 넘는 비율에 건성안 유무에 따른 유의한 차이가 있었다(p=0.033, 0.037). NIKBUT-average와 각막곡률 값 차이의 절대값에 대하여 선형회귀분석 시행 시 최대각막곡률과각막난시에서 유의한 음의 상관관계를 보였다(p=0.030, R2=0.134 and p=0.017, R2=0.160). 결론: 건성안 환자에서 K5M으로 측정한 각막곡률계측의 재현성은 높았으나 정상 대조군에 비해서는 다소 떨어지며, 각막곡률계측의유의한 차이를 보이는 비율이 건성안 유무에 따라 차이가 있었다. 또한 건성안에서 비침습눈물막파괴시간이 낮을수록 각막곡률 값의측정의 재현성은 낮아질 수 있어서 심한 건성안군에서는 각막곡률측정에 주의할 필요가 있겠다. Purpose: To evaluate the effects of the non-invasive keratograph break-up time on the repeatability of keratometric measurements derived using the Keratograph 5M in patients with dry eye syndrome. Methods: Thirty-six patients with dry eye and 30 controls were enrolled. We measured keratometric values twice in all subjects and explored whether the two measurements differed by more than 0.5 diopter (D) (the absolute value). We also evaluated the relationship between the absolute difference and the non-invasive keratograph break-up time (NIKBUT). Results: The intraclass correlation coefficients for astigmatism, flat keratometry (K), steep K, and mean K were all higher than 0.95 in patients, thus lower than in controls. The proportion of eyes with absolute differences over 0.5 D between the two keratometric values differed significantly between the dry eye and control groups in terms of the flat K and Kmax values (p = 0.033, 0.037). The average NIKBUT was negatively correlated with the absolute differences in Kmax and astigmatism (p = 0.030, R2 = 0.134 and p = 0.017, R2 = 0.160). Conclusions: In patients with dry eye syndrome, keratometric measurements are reliably repeatable, but slightly less so than in normal controls. The proportions of eyes exhibiting absolute keratometric differences over 0.5 D (two measurements) differed in the dry eye and control groups. The lower the non-invasive keratograph break-up time, the poorer the repeatability of keratometric measurements in the dry eye group. Therefore, care is required when obtaining keratometric values for such patients. KCI Citation Count: 0